ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS X IPA SMAN 5 PADANG - FADILLA VIONITA (Jurnal Edukasi dan Penelitian Matematika, 2021)
Analysis of students' ability to understand mathematical concepts is one of the things that is important to do to obtain information on  students’ abilities in understanding the material. Based on data in the field, students in class X SMAN 5 Padang are thought to have low concept understanding skills. This research uses a qualitative approach with descriptive research type. The results showed that the average score of the ability to understand mathematical concepts on indicator 1 was 0.36 with a very low category, indicator 2 was 0.62 in the moderate category, indicator 3 was 0.37 in the very low category, indicators 4 and 5 were 0.4 in the low category.Keyword--concept understanding ability